PEMETAAN PROFIL PASIEN/KLIEN RUMAH SAKIT UMUMDAERAH (RSUD) KOTA X MENGGUNAKAN NET PROMOTER SCORE - Roselina, Elsa (UI Scholars Hub, 2016)
Regional General Hospital City X is the only government-owned hospitals of city X, had some vision including provide excellent service quality plenary to the whole society. Net Promoter Score (NPS) is a tool and concept of customer satisfaction, which through NPS companies can see their performance according to the customer's perspective. This study aimed to obtain consumer profiles and identify strengths and weaknesses in the service of the Regional General Hospital City X based on the perception of consumers. This study used a quantitative approach with survey method. Data captured in one shoot measurement from August until September 2015. Instruments used in the form of a questionnaire. The research subjects were patients/families undergoing outpatient treatment or hospitalization in some treatment rooms of the Regional General Hospital City X. The total sample was 442 persons, calculated using the Slovin formula with alpha 0.05. The analysis was univariate analysis. The final results showed the profile of patients/families mostly as consumers detractors (45.2%) than consumers promoters (19.7%), where the value indicated by the NPS better perception of inpatients than outpatients. Weakness in outpatient services is a long queue system and the limited facilities, whereas in inpatient facilities are limited and hygiene problems. City Hospital X strength in providing services is the friendliness of its officers (doctors, nurses, administration).